A New Scheme to Direct Torque Control of Matrix Converter-Fed Five-Phase Permanent Magnet Synchronous Motor - Gholamian, Sayyed Asghar (Journal of Science and Technology, 2013)
Multiphase machines have gained an increasing attention due to their more advantages in comparison with three-phase machines. In recent literatures, only voltage source inverters (VSIs) have been used to supply five-phase drives. Matrix converters (MCs) pose many advantages over conventional VSIs, such as lack of dc-bulk capacitors, high quality power output waveform and higher number of output voltages. Due to some special applications of multiphase machines such as ship propulsion and aerospace, the volume of these drives is an important challenging problem. As a consequence, using MCs can be a reasonable alternative. In this paper, a new direct torque control (DTC) algorithm using a three-to-five phase MC is proposed for five-phase permanent magnet synchronous motors (PMSMs). All of output voltage space vectors of three-to-five phase MC are extracted and a new switching table is proposed. Because of higher number of output voltages in MCs, there is a degree of freedom to control input power factor to keep close to unit moreover the torque and flux control. In other words, this proposed method use the advantages of both DTC method and MCs. Simulation results show the effectiveness of presented method in different operation modes.